Correlating 2-MIB and microcystin concentrations with environmental parameters in two reservoirs in South Taiwan - Yen, H (Water science and technology : a journal of the International Association on Water Pollution Research, 2007)
Cyanobacteria are present in many drinking water reservoirs in Taiwan, and some of them may produce off-flavour compounds and natural toxins. To investigate the correlation among two groups of cyanobacterial metabolites, microcystins and 2-methylisoborneol (2-MIB), and other environmental parameters, approximately 22 water quality and meteorological parameters were monitored for two source waters (Moo-Tan and Tseng-Wen reservoirs) in south Taiwan from August 2003 to April 2005. Monitoring results showed that the two groups of cyanobacterial metabolites were present in the source waters. Concentrations of 2-30 ng/L of 2-MIB was observed for the two reservoirs, while that of the total concentrations of the five microcystin congeners measured were between 30 and 340 ng/L. The concentration of both 2-MIB and microcystins showed higher concentrations in warmer seasons. A stepwise regression technique was employed to correlate 2-MIB and microcystins concentrations with all the corresponding water quality and meteorological parameters. Correlations among 2-MIB concentration, microcystin concentration, water temperature and air temperature were found in the water samples collected from both reservoirs. The correlations may provide a simple means for the water utility to anticipate the two groups of cyanobacterial metabolites in the two source waters